Industrial Design Digital Technology. (2015) - Loy, J.; Canning, S.; Little, C.
Abstract: This paper is a reflective opinion piece suggesting that the Industrial Design discipline has an opportunity to react proactively to disruptive practices made possible by innovations in digital technology, by developing a field of practice in 'Industrial Design Digital Technology' that challenges the boundaries of the current Industrial Design discipline and potentially stimulates new directions for the profession and for graduates. This would also provide an opportunity for new research collaborations that are in line with the demand for more interdisciplinary work in higher education, creating genuinely transdisciplinary practice that will attract funding and attract students.